Comarative analysis of the development of small enterpreneurship in the European Union and Russia - L. F. Sultanova (Путеводитель предпринимателя)
In the article there presented the ananlysis and there opened out main problems of the development of small enterpreneurship in the European Union and Russia, as well as there considered instruments applied by the government for the development of small business and the assessment of regulatory impact of legal acts. According to the results of the research there systematized the problems ofSME-test realization in Russia and there suggested some recommendations.